Hubungan Antara Pengaruh Keluarga, Teman, Iklan Terhadap Perilaku Merokok Pada Siswa Di SMPN 6 Wonogiri - Sari, Dian Puspita, Abi Muhlisin, SKM, M.Kep, Kartinah, A.Kep, S.Kep (2016)
The habit of teenager that is difficult to be avoided is the smoking behavior. The smoking behavior is influenced by many kinds of factors, such as the influence of family, the influence of friends, and the influence of advertisement. If one of family members smokes, either father or older brother, there is a possibility that the behavior will be imitated by children to smoke. Peers are also very influential in the teenagers' smoking behavior. Besides, media broadcasting on television, newspapers, and banners on roads are also influential on the children's smooking behavior. The objective of this research was to know how big the influences of family, friends, and advertisement were on the male students' smoking behavior in SMP N 6 Wonogiri. The design used was descriptive quantitative with a cross sectional design. Population in this research was all male students of SMP N 6 Wonogiri, meanwhile, sample taken was as many as 73 male students. The sample was taken from each class as many as 3 to 5 male students. The technique of sample in this research used random sampling. The technique of data analysis used Chi-Square (χ2) test. The result of analysis of Chi-Square (χ2) test between the influence of family and the smoking behavior of the students in SMP N 6 Wonogiri was (χ2 hit = 7,193 ; ρ = 0,027); the result of analysis of Chi-Square (χ2) test between the influence of friends and the smoking behavior of the students in SMP N 6 Wonogiri was (χ2 hit = 7,106 ;ρ = 0,029); the result of analysis of Chi-Square (χ2) test between the correlation of the influence of advertisement and the smoking behavior was that there is a significant correlation between the influence of advertisement and the smoking behavior of the students in SMP N 6 Wonogiri (χ2 hit = 6,699 ; ρ = 0,035). Suggestion for the future researchers was that the researchers are able to conduct a similar research that studies other factors that influence the smoking behavior which were not examined in this research.